2016
DOI: 10.4103/1319-3767.195550
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac functions assessment in children with celiac disease and its correlation with the degree of mucosal injury: Doppler tissue imaging study

Abstract: Background/Aims:Celiac disease (CD)-associated cardiologic disorders is a growing concern. However, data regarding cardiac affection in children with CD are few. This study aimed at assessing the subclinical impact of CD on the global myocardial performance in Saudi children with CD using Doppler tissue imaging (DTI).Patients and Methods:Conventional two-dimensional echocardiography was performed among 20 Saudi children with CDas well as 20 age and sex-matched healthy controls. DTI were used to determine right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…In our study, there was no significant cardiac dysfunction between patients and controls according to conventional echocardiography in accordance with the literature 8,19 . However, when evaluated by TDI echocardiography, it was shown that both the left ventricle and the right ventricle had systolic and diastolic dysfunction in the patient group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, there was no significant cardiac dysfunction between patients and controls according to conventional echocardiography in accordance with the literature 8,19 . However, when evaluated by TDI echocardiography, it was shown that both the left ventricle and the right ventricle had systolic and diastolic dysfunction in the patient group.…”
Section: Discussionsupporting
confidence: 92%
“…Because of this data, recent investigations have focused on noninvasive echocardiography methods that can detect subclinical myocarditis. In a small number of studies in children with CD, early cardiac involvement has been shown to be detectable by TDI echocardiography 8,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to obtained data regarding cardiac involvement in patients with CD, recent studies focused on noninvasive echocardiographic methods which can detect subclinical carditis before development of potential dilated cardiomyopathy . A few studies have indicated that early cardiac involvement in patients with CD can be detected by TDI echocardiography in both adults and children . In our study, none of the patients with CD had LV systolic and diastolic dysfunctions according to conventional echocardiography.…”
Section: Discussionmentioning
confidence: 42%
“…15 A few studies have indicated that early cardiac involvement in patients with CD can be detected by TDI echocardiography in both adults 16,17 and children. [18][19][20] In our study, none of the patients with CD had LV systolic and diastolic dysfunctions according to conventional echocardiography. Despite the similarities in previous studies and our study, in terms of the size of the study population, the duration of CD and the age of patients, we did not detect any difference between patient and control groups by TDI echocardiography.…”
Section: Discussionmentioning
confidence: 52%
“…Patients with CD can have impaired diastolic and systolic function as measured by tissue Doppler echocardiography[ 141 ]. Mitral valve prolapse[ 142 ] and subclinical myocardial dysfunction of both ventricles[ 143 ] can be present in both the pediatric and adult CD population. In children, significantly lower contractility indices and higher left ventricular dimensions are evident as compared with controls[ 144 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%